Enhancement of heat transfer in a pipe with inner contraction-expansion-contraction pipe insertion - Öztop, Hakan Fehmi; Dagtekin, I (Pergamon-Elsevier Science Ltd, 2003)
In this study, a numerical analysis was conducted in order to enhance heat transfer in a circular smooth pipe. As a physical configuration a partly heated circular pipe with an inner contraction-expansion-contraction (CEC) pipe insertion was considered. Due to the insertion of the CEC pipe some amount of fluid is deviated from the original path to the heated pipe, thus, the heat transfer increases from the heated wall to the fluid. A finite control volume approach was applied for discretisation of transport and energy equations in laminar flow regime. The calculations were performed for various Reynolds numbers ranging from 100 to 1000, various Prandtl numbers ranging from 0.1 to 10 and at the different CEC ratio beta (= r(2)/r(1)) values. It is found that Peclet number and beta values affect the heat transfer enhancement significantly and average CEC beta(1) (= r(3)/r(0)) values should be less than 0.7 in order not give rise to severe pressure drop. (C) 2003 Elsevier Science Ltd.
Keywords: In-Line; Flow; Exchangers